Transformation of the principles of administrative procedure in the administrative proceedings - Гончарук, Степан Тихонович; Бєлкін, Леонід Михайлович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2014)
In this paper, based on the current national legislation, taking into account the specifics of a particular transformation the authors study principles of administrative procedure in administrative proceedings, their system and content. The legal principles generally are understood as the fundamental, guiding ideas, the basic assumptions and patterns upon which certain legal activities and legal phenomena are based. Administrative-procedural principles can be determined as a basic guiding idea on which the administrative and procedural activities as to the consideration and resolution of specific individual administrative cases in public administration are based.